Solarise : solar branding through the culture lens of Tri Hita Karana : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, New Zealand - Jessica, Victoria (Massey University, 2024)
The project is an enquiry into a cultural approach to branding. It utilises a holistic process inspired by a Balinese moral compass, the Tri Hita Karana, which is a balance between humans, nature, and spiritual aspects. The project explores through branding a solar organisation that seeks to promote sustainability and the beneﬁts of solar energy through a visual communication design system. Bali, an island in Indonesia, is currently experiencing a power shortage due to its high electricity demand and being the last in the transmission line from Java island. Solar power is a viable substitute for fossil fuels to address the issue, as Bali receives plenty of sunlight. However, the need for more public awareness about solar energy and sustainability hinders the solar movement. This research aims to communicate its purpose and meaning e ectively by adopting a cultural branding approach emphasising the rich cultural aspects of Bali through visual language and graphic elements. The goal is to encourage a shift in behaviour and attitude towards clean energy technologies as part of the energy transition movement. The project uses cultural brand theories and energy transition frameworks to approach Balinese culture empathetically. The objective of this master's project is to explore the narratives of Balinese culture and ﬁnd ways to create a brand identity system that synergises with these elements. A website, out-of-home QR codes, and social media are part of the visual communication design research outcomes. The narrative of the outcomes intends to increase awareness and support positive initiatives for rebuilding sustainability in Bali. It emphasises the connection between humans, nature, and spirituality while highlighting solar panels' beneﬁts and their connection to the brand.
Figures are reproduced with permission.
Keywords: Energy Transition; Influence; Tri Hita Karana; Cultural Branding; Connection; Life Moral Compass; Balance; Sustainability; 330316 Visual communication design (incl. graphic design); 350602 Consumer-oriented product or service development